Pengaruh Green Accounting dan Kinerja Lingkungan terhadap Nilai Perusahaan: Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI periode 2020-2024 - Fikrul Rezki; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2026)
The purpose of this study is to examine how green accounting and environmental performance affect company value. This study used a causal research design and a quantitative technique. The annual reports of mining subsector businesses registered on the Indonesia Stock Exchange (IDX) between 2020 and 2024 provided secondary data. Purposive sampling was the method employed, yielding a sample of 23 businesses. The Ministry of Environment and Forestry's PROPER grade was used to evaluate environmental performance, and the annual reports of the companies were used to gauge green accounting by disclosing environmental costs. The Tobin's Q ratio was used as a stand-in for firm value. Profitability and firm size were also added as control variables. Using panel data regression analysis and EViews version 12 software, hypothesis testing was done. According to the study's findings, environmental performance significantly and favorably affects corporate value, whereas green accounting has no discernible influence.